PROSOCIAL BEHAVIOR IN ISLAMIC PSYCHOLOGY - Ilmiyati Refi Fadlia; Casmini Casmini (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2024)
Nowadays, there has been a decline in morality toward others. It is resulting in various problems, such as bullying, theft, promiscuity, alcohol, drugs, death due to social media violence, and anxiety. The variety of conflicts that occur means that prosocial behavior is needed to minimize the conflicts that arise. Prosocial behavior is defined as behavior that positively impacts the individual himself or others. This research aims to find out how prosocial behavior is from the perspective of Islamic psychology. This research uses a literature study type of research (literature review). This research uses books and articles relevant to the author's discussion as the primary data sources for obtaining research related to prosocial behavior. This research shows that in Islamic psychology, prosocial behavior is in the form of helping; in surah al-maida verse 2, the words birr and piety are mentioned. Where birr means all good deeds, taqwa means fear of Allah, avoiding Allah's prohibitions, and carrying out Allah's commands.